Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region - Fusari, Lívia Maria; Dantas, Galileu P.s.; Hamada, Neusa; Andrade-Souza, Vanderly; Lima, Kátia M.; Silva, Janisete G. (Zootaxa, 2018)
Imparipecten, a previously monotypic genus, was considered endemic to Australia. Here, we report Imparipecten from the Neotropical region for the first time and describe Imparipecten sychnacanthus sp. n. from Brazil. The association between larvae and adults was established by sequencing a fragment of one ribosomal gene (28S), two fragments of a nuclear protein-coding gene (CAD1 and CAD4), and one mitochondrial protein-coding gene (COI). We also show the close molecular proximity with Imparipecten pictipes through analyses of genetic distances and Bayesian phylogenetics.